Correlation of percentage and intensity of CPB attacks on production and loss of products due to various levels of cocoa plantation care - Mulyani Cut; Iswahyudi Iswahyudi (E3S Web of Conferences, 2023)
Aceh Tamiang District is currently developing cocoa plantations. The cocoa plantation management problem is the high attack of Plant Pest Species, especially the Cocoa Pod Borer (CPB), which causes cocoa productivity to decline. This study aimed to determine the percentage and intensity of CPB pests attacks on cocoa plantations. This research was carried out in three sub district in Aceh Tamiang District, Aceh Province. The research location was determined purposively. The selected garden samples had four different care levels: not being treated for, being treated for in moderation, being treated conventionally and practicing IPM. The results showed that CPB pests attacked all of the cacao plantation maintenance criteria. In sequence, the percentage and intensity of CPB pest attacks from the highest to the lowest were found in the criteria for farm care that practiced IPM, were treated conventionally, were treated for and not treated. The farms that were not treated had the highest percentage of attacks and CPB attack intensity. The lowest percentages in the criteria of farms that have been treated with IPM practice. The regression analysis of the relationship between the intensity of the attack and the loss of yield due to the CPB attack. The results showed that the levels of incursions by CPB pests was different depending on the classification level of the plantation The findings highlighted the importance of implementing the practice of IPM to reduce instances of CPB incursion.